2011
DOI: 10.1007/s12098-011-0396-y
|View full text |Cite
|
Sign up to set email alerts
|

Inadequacy of Present Polyspecific Anti Snakevenom— A Study from Central Kerala

Abstract: Hump nosed pit viper envenomation is not rare in Kerala and can cause death, unlike the earlier belief. Available anti snake venoms does not cover pit viper. So, antivenom for this snake is urgently required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…The clinical features and complications noted in our sample are comparable with the findings from previous studies in children and adults 3 8 9…”
Section: Discussionsupporting
confidence: 89%
“…The clinical features and complications noted in our sample are comparable with the findings from previous studies in children and adults 3 8 9…”
Section: Discussionsupporting
confidence: 89%
“…[345678] South Indian snakes predominantly cause hemotoxicity or nephrotoxicity in 83.59% of cases (1965 envenomations) [Table 1]. [910111213141516] This trend becomes apparent as we move Southward from Delhi early as Maharashtra, which has thus been included by us in South India. North Indian snakes predominantly cause neurotoxicity in 70.95% of cases (877 envenomations) [Table 2].…”
Section: Introductionmentioning
confidence: 99%
“…[345678] P < 0.05 Our research shows that the Russell's viper is virtually nonexistent in North, and there is enough published evidence to prove this fact. [345678910111213141516] Neurotoxic snake Krait is responsible for high mortality throughout North India. [345678] Hence, the North Indian profile is neurotoxicity predominant (Krait), and South Indian profile is hemonephrotoxicity predominant (Russell's and saw-scaled vipers).…”
Section: Introductionmentioning
confidence: 99%
“…In southwestern India (Kerala), in the year 2007, H. hypnale was identified as a common and dangerous source of envenoming, second only to Russell's viper. Deaths have been subsequently recorded in India following HNV envenoming [5,10]. In a prospective multicenter study involving ten hospitals in Sri Lanka, 302 HNV bite victims were identified out of 860 patients with bites by identified snakes (35%).…”
Section: Reviewmentioning
confidence: 99%